Perancangan Sistem Informasi Prepaid di Perusahaan Makanan Siap Saji XYZ - J. Rolles Herwin Sihombing; Selvyna Theresia (ComTech: Computer, Mathematics and Engineering Applications, 2015)
Prepaid System becomes a new trend in the Indonesia retail industry, particularly in the Food and Beverage (F&B) sector. Many companies are trying to develop their own prepaid system, however they still lack of skills and knowledge regarding this system. This condition might not enable them to deliver the prepaid system to customers properly if they insist to develop their own system. However, this does not happen to company XYZ, the biggest fast food restaurant in Indonesia. Company XYZ, which collaborates with the local partner, implements their own prepaid system in their company. This local partner has already had years of experience in the payment industry, developing payment system that adapts to the latest technology and supports the company's business. A system that is integrated with the point-of-sales and website would absolutely help customer and cashier in doing the transaction process. Integrated data is very useful for the finance and accounting departments of Company XYZ providing annual financial report to the shareholders.